Burnout among workers in emergency Departments in Palestinian hospitals: prevalence and associated factors - Motasem Hamdan; Asma'a Abu Hamra (BMC, 2017)
Abstract Background Working in Emergency Departments (EDs) entails high work pressure and stress due to witnessing human suffering and the unpredictable nature of the work. This environment puts personnel at risk of burnout. This analysis aims to assess burnout levels and associated risk factors among health workers in EDs in Palestinian hospitals. Also, it examines the association between burnout and workplace violence, as well as with job turnover. Methods Cross-sectional design utilising a self-administered questionnaire was used to collect data from all workers at 14 EDs; 8 from the West Bank and 6 from the Gaza Strip. Burnout was measured using Maslach Burnout Inventory-Human Services Survey. Results A total of 444 workers (response rate 74.5%) participated: 161(36.3%) nurses, 142(32.0%) physicians and 141(31.7%) administrative personnel. Results showed high levels of burnout among EDs workers; 64.0% suffered from high emotional exhaustion, 38.1% from high depersonalization and 34.6% from low personal accomplishment. In addition, high levels of emotional exhaustion (72.3%) was significantly prevalent among physicians compared to nurses (69.8%) and administrative workers (51.4%) (p < 0.05). In comparison, high levels of depersonalization was significantly prevalent among nurses (48.8%) compared to physicians (32.1%) and administrative workers (31.9%) (p < 0.05). However, there were no significant differences in the levels of personal accomplishment burnout among the three groups (p > 0.05). Moreover, high degree of burnout was more prevalent among EDs workers in the West Bank than among those working in the Gaza Strip (OR 2.02, 95% CI = 1.11-3.69, p = 0.019), and higher among younger workers (aged ≤30 years old) than their older counterparts (OR 2.4, 95% CI = 1.302-4.458, p = 0.005). Exposure to physical violence was significantly associated with having a high degree of burnout (OR 2.017 95% CI = 1.121-3.631, p = 0.019), but no association was observed with regards to exposure to verbal violence (p > 0.05). Finally, burnout was significantly associated with workers' intention to leave work at EDs (p < 0.05). Conclusions Burnout is considerably prevalent among EDs' workers, especially nurses and physicians. Burnout is positively associated with job turnover intention and also with exposure to workplace violence. Therefore, there is a need for prevention and management strategies to address occupational burnout and reduce negative consequences on workers, patients and organisations.